Effect of Visual Impairment on Physical and Cognitive Function in Old Age: Findings of a Population‐Based Prospective Cohort Study in Germany. Issue 11 (27th September 2016) - Hajek, André; Brettschneider, Christian; Lühmann, Dagmar; Eisele, Marion; Mamone, Silke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Fuchs, Angela; Riedel‐Heller, Steffi G.; Luck, Tobias; et al.
Abstract : Objectives: To examine how visual impairment affects physical and cognitive function in old age. Design: A longitudinal population‐based prospective cohort study. Setting: General practitioner offices at six study centers in Germany. They were observed every 1.5 years over four waves. Participants: Individuals aged 77–101 at follow‐up Wave 2 (N = 2, 394). Measurements: Physical and cognitive function were assessed using an adapted scale that had been previously developed, and visual impairment was rated on a Likert scale (none, mild, severe or profound). Results: Adjusting for sociodemographic factors and comorbidity, linear fixed‐effects regression showed that the onset of severe visual impairment was associated with a decline in physical function score in the total sample ( β = −0.15, P = .01) and in women ( β = −.15, P = .03). Moreover, the onset of severe visual impairment was associated with decline in cognitive function score in the total sample ( β = −0.38, P < .001) and in women ( β = −0.38, P < .001) and men ( β = −0.37, P = .001). Conclusion: Visual impairment affects physical and cognitive function in old age. Interventional strategies to postpone visual impairment may contribute to maintaining physical and cognitive function.